46th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2010
DOI: 10.2514/6.2010-6557
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Pressure Measurements for Unstart Detection in Scramjet Isolators

Abstract: This paper describes an experimental investigation using an array of high-frequency pressure transducers located in the isolator/combustor region of a direct-connect hydrocarbon-fueled, scramjet combustor. Isolator/combustor entrance conditions were fixed and representative of a Mach-5.5 flight condition. Mean, standard deviation, and spectral content of measured pressures were similar to those measured in previous studies. A simple model relating the sum of measured pressures and the fuel flow rate delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…If the heat release in the combustor is sufficiently large at a given instant in time, the pressure rise cannot be accommodated within the given isolator length. In such an instance, the shock train could be forced upstream out of the isolator and could induce inlet unstart [4]. A cavity could be inserted in the isolator section to control the shock train and to arrest the potential upstream movement of the shock train.…”
mentioning
confidence: 99%
“…If the heat release in the combustor is sufficiently large at a given instant in time, the pressure rise cannot be accommodated within the given isolator length. In such an instance, the shock train could be forced upstream out of the isolator and could induce inlet unstart [4]. A cavity could be inserted in the isolator section to control the shock train and to arrest the potential upstream movement of the shock train.…”
mentioning
confidence: 99%
“…Instantaneous high thermal energy release in the combustor could significantly increase the backpressure and force the shock train out of the isolator into the inlet. 8 This phenomenon, termed unstart, must be prevented for stable scramjet operation. It has been demonstrated that a resonating cavity can increase the downstream blockage needed to unstart a model isolator (straight duct) 9 ; however, no optimization of the cavity geometry for this purpose was pursued.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have been conducted implementing various schemes including summation of pressures, power spectral density change detection algorithms, and other novel approaches. [6][7][8][9][10][11] A final aspect of the unstart problem that has been investigated consists of research into preventing or controlling the unstart process. Investigations into unstart prevention and shock position control have been conducted with varying levels of success.…”
Section: Introductionmentioning
confidence: 99%